2017
DOI: 10.1016/j.euroecorev.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The value and motivating mechanism of transparency in organizations

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP url' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Additionally, workers in the treatment No Delegation have been given an explanation for the change in the organization's policy—A plausible behavior of an employer who does not want to explicitly antagonize workers. Accordingly, workers receive both information and recognition from their employer which has been shown to be highly valued by workers, even in the case of bad news (see, e.g., Brandes & Darai, ; Kosfeld & Neckermann, ). Besides, not necessarily every employee values wage delegation as a signal of benevolence from the employer: Psychological and economic research (see, e.g., Irons & Hepburn, ; Iyengar & Lepper, ) has shown that an individual's desire for choice is sometimes limited so that the choice might therefore be seen as a burden rather than a gift.…”
Section: Behavioral Predictionsmentioning
confidence: 99%
“…Additionally, workers in the treatment No Delegation have been given an explanation for the change in the organization's policy—A plausible behavior of an employer who does not want to explicitly antagonize workers. Accordingly, workers receive both information and recognition from their employer which has been shown to be highly valued by workers, even in the case of bad news (see, e.g., Brandes & Darai, ; Kosfeld & Neckermann, ). Besides, not necessarily every employee values wage delegation as a signal of benevolence from the employer: Psychological and economic research (see, e.g., Irons & Hepburn, ; Iyengar & Lepper, ) has shown that an individual's desire for choice is sometimes limited so that the choice might therefore be seen as a burden rather than a gift.…”
Section: Behavioral Predictionsmentioning
confidence: 99%
“…Many researchers continue to refer to a pay secrecy (Belogolovsky & Bamberger, 2014; Blumkin & Lagziel, 2019) or a pay transparency continuum (Brandes & Darai, 2017; Cullen & Pakzad-Hurson, 2019). Others refer to a pay communication scale with pay secrecy and pay openness (Marasi, Wall, & Bennett, 2018) or pay transparency representing the two anchors.…”
Section: Pid: Conceptualizationmentioning
confidence: 99%
“…Therefore, transparency has value. and the paradox when involving it in organizations is evident [36,39], which makes some control and structure mechanisms over information technology necessary. Such mechanisms meet the strategic management demands.…”
Section: Organizational Transparencymentioning
confidence: 99%